MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA SISWA KELAS VI SD NEGERI 138 PALEMBANG - Rusmiati Rusmiati (Universitas Negeri Medan, 2021)
Abstract: Improving Mathematics Learning Outcomes Using the Jigsaw Type Cooperative Learning Model for Class VI Students of SD Negeri 138 Palembang. The purpose of this action research is to find out the improvement of mathematics learning outcomes after the application of the Jigsaw type cooperative learning model to the sixth grade students of SD Negeri 138 Palembang. The subjects in this study amounted to 25 students. This study uses classroom action research which was conducted in two rounds. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the data analysis obtained that student learning outcomes have increased significantly. The increase in learning outcomes is marked by an increase in student learning mastery in each cycle, namely the cycle reaches the initial condition (28%), cycle I (68%) and cycle II (88%). From the results of data analysis, it can be concluded that the peer tutor type cooperative learning model can have a positive effect on increasing the activity and learning outcomes of sixth grade students at SD Negeri 138 Palembang, and this learning model can be used as an alternative in further Mathematics learning.Keywords: Learning Outcomes, Jigsaw, MathematicsAbstrak: Meningkatkan Hasil Belajar Matematika Menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw Pada Siswa Kelas VI SD Negeri 138 Palembang.Tujuan dari penelitian tindakan ini adalah mengetahui peningkatan hasil belajar Matematika setelah diterapkannya model pembelajaran kooperatif tipe Jigsaw pada siswa kelas VI SD Negeri 138 Palembang. Adapun subjek dalam penelitian ini berjumlah 25 orang siswa. Penelitian ini menggunakan penelitian tindakan kelas (classroom action research) yang dilakukan sebanyak dua putaran. Setiap putaran terdiri dari empat tahap yaitu: rancangan, kegiatan dan pengamatan, refleksi, dan revisi. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil analis data diperoleh bahwa hasil belajar siswa mengalami peningkatan yang signifikan. peningkatan hasill belajar tersebut ditandai dengan peningkatan ketuntasan belajar siswa dalam setiap siklusnya, yaitu siklus mencapai kondisi awal (28 %), siklus I (68 %) dan siklus II (88%). Dari hasil analisis data diperoleh dapat disimpulkan bahwa model pembelajaran kooperatif tipe tutor sebaya dapat berpengaruh positif terhadap peningkatan aktivitas serta hasil belajar siswa kelas VI SD Negeri 138 Palembang, serta model pembelajaran ini dapat digunakan sebagai salah satu alternatif dalam pembelajaran Matematika selanjutnya.Kata Kunci: Hasil Belajar,Jigsaw, Matematika